PANDANGAN FARID ESACK TENTANG AL-QUR’AN, TAFSIR DAN TAKWIL SERTA IMPLIKASINYA TERHADAP BANGUNAN TEOLOGI PEMBEBASAN - Zunly Nadia (AN NUR: Jurnal Studi Islam, 2012)
Farid Esack, an intellectual from South Africa, tries to give his interpretation concerning with the condition and situation of African society that is in the oppression of the apartheid regime. Here, Esack has attention to methodological issues of interpretation. In this case, he offers his hermeneutics of Qur’an because, according to Esack, interpretation of the Qur’an that has been performed all this time is done without having a systematic methodological foundation. This hermeneutics of the Qur’an then has implications for the building of liberation theology which tries to answer the social problems faced because, according to Esack, Qur’an is basically not only a holy book which contains the teachings of a religious ritual, but moreover, the Qur’an also brings mission of emancipation for humanity.